Trade liberalization and the evolution of skill earnings differentials in Brazil - Gustavo Gonzaga; Naércio Menezes Filho; Cristina Terra (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
Skilled labor earnings differentials decreased during the trade liberalization implemented in Brazil from 1988 to 1995. This paper investigates the role of trade liberalization in explaining these relative earnings movements. We perform several independent empirical exercises that check the traditional trade transmission mechanism, using disaggregated data on tariffs, prices, earnings, employment and skill intensity. We find that: i) employment shifted from skilled to unskilled intensive sectors, and each sector increased its relative share of skilled labor; ii) relative prices fell in skill intensive sectors; iii) tari changes across sectors were not related to skill intensities, but the pass-through from tariffs to prices was larger in skill intensive sectors; iv) the decline in skilled earnings differentials mandated by the price variation predicted by trade was even larger than the observed one. The results are compatible with trade liberalization accounting for the observed relative earnings changes in Brazil. They also highlight the importance of considering the effects of differentiated pass-through from tariffs to prices.
Keywords: F13; J21; 330; Skill Earnings Differentials; Trade Liberalization; Tariffs Pass-through; Stolper-Samuelson; Handelsliberalisierung; Lohnstruktur; Qualifikation; Brasilien